Trustworthy E-Commerce Model for Small Medium Enterprises (SMEs) - F.H.O, Hamed; M.S, Madihah; S, Kamaruzzaman (International Journal of Engineering and Technology, 2018)
This paper presents a trustworthy model for an e-commerce website consisting of technologically-driven factors that influence the e-commerce usage and by employing the Theory of Planned Behaviour as the basis of developing the model. For this paper, self-administered survey questionnaires were distributed to 600 respondents at small medium enterprises (SMEs) in Libya, the structural equation modeling (SEM) was utilized to test the factor analysis. Based on 296 of 600 respondents of the administered questionnaires, the results showed that the perceived ease of usage and perceived ease of trust are highly significant when it comes to the usage of ecommerce. Both parameters recorded a preference score of 52% and 36% respectively. As a result, these two factors are considered to be the main factors that influence the e-commerce usage by SMEs in Libya.Â